ARBUSCULAR MYCORRHIZAL FUNGI FROM THE RfflZOSPHERES OF SOYBEAN CROPS IN LAMPUNG AND WEST JAVA*) - K. KRAMADIBRATA; E.I. RIYANTI; R.D.M. SIMANUNGKALIT (BIOTROPIA, 1995)
The occurrence of arbuscular mycorrhizal (AM) fungi in the rhizospheres of field-grown soybean crops in the provinces of Lampung and West Java was examined. Nineteen taxa of AM fungi were identified as follows: Acaulospora delicata, A. Foveata, A. rehmii, A. scrobiculata and A. tuberculata; Gigaspora cf. gigantea and Gigaspora sp. 1; Glomus clavisporum; Glomus cf. fasciculatum, Glomus micro-aggregatum, Glomus sp. 1, Glomus sp. 2, Glomus sp. 3 and Glomus sp. 4; Scutellospora cf. heterogama, Scutellospora cf. pellucida, Scutellospora sp. 1. Scutellospora sp.2. and Scutellospora sp. 3. Key words: Mycorrhizas/Soybean/Rhizosphere fungi/Identification.